Molecular markers applied to genetic diversity analysis and genome - wide association studies for micronutrients in grains and biotic stresses traits in barley (Hordeum vulgare L.) - NYIRAGUHIRWA, Solange; Ndayisenga, Valence; Grana, Zahra; Hiddar, Houda (Algerian Journal of Biosciences, 2023)
The cultivated barley (Hordeum vulgare L.) ranks the fourth most important cereal worldwide. It feeds animals, produces malt, and is used in the human diet. Yield increase and yield stability are the top barley breeding goal. However, diseases such as the Net form of Net blotch (NFNB) and powdery mildew (PM) reduce yield and grain quality. For barley destined for human consumption, micronutrients increase in grains, especially zinc and iron, is essential to alleviate malnutrition. Thus, breeders must select new loci and use them to develop higher-yielding, nutritious, and disease-resistant cultivars. This study reviews the importance of genetic diversity analysis using molecular markers and Genome-wide association studies (GWAS) in barley breeding. Genetic diversity studies are crucial for conservation and utilization of barley germaplasm in plant breeding. Secondly, we discuss genome-wide association study (GWAS) uses to locate genomics regions associated with important barley traits such as disease resistance to NFNB and PM, and micronutrients (Zn and Fe) content in grains. Significant SNP identified in GWAS studies once validated in other experiments or populations, they can be converted into user-friendly markers and used to develop barley cultivars with improved quality, and disease resistance via marker-assisted selection.